A case of Pfeiffer syndrome with c833_834GC>TG (Cys278Leu) mutation in the gene - Min Young Lee; Ga Won Jeon; Ji Mi Jung; Jong Beom Sin (Korean Pediatric Society, 2010)
Pfeiffer syndrome is a rare autosomal dominant disorder characterized by coronal craniosynostosis, brachycephaly, mid-facial hypoplasia, and broad and deviated thumbs and great toes. Pfeiffer syndrome occurs in approximately 1:100,000 live births. Clinical manifestations and molecular genetic testing are important to confirm the diagnosis. Mutations of the fibroblast growth factor receptor 1 (FGFR1) gene or FGFR2 gene can cause Pfeiffer syndrome. Here, we describe a case of Pfeiffer syndrome with a novel c833_834GC>TG mutation (encoding Cys278Leu) in the FGFR2 gene associated with a coccygeal anomaly, which is rare in Pfeiffer syndrome.